2019
DOI: 10.5430/jnep.v10n4p21
|View full text |Cite
|
Sign up to set email alerts
|

Peer support for undergraduate children’s nursing students

Abstract: Background and objective: The provision of appropriate ‘pastoral’ support for nursing students is acknowledged to be problematic for a variety of reasons, (time constraints, staffing levels, unmanageable workloads). The need to initiate and access more suitable support is imperative – particularly in the light of the increasing number of students suffering with mental health issues. This study examines the dynamics of a student peer support programme over a two-year period. Twenty-one first year students (chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Interventions to increase social integration and support for student nurses may be beneficial. Peer support programmes have valuable personal and professional effects for nursing students (Carey et al., 2018; Cust & Guest, 2019), and may be preferred to professional help (Morton, 2022). Studies concerning nursing students outside of their country of origin were not identified.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to increase social integration and support for student nurses may be beneficial. Peer support programmes have valuable personal and professional effects for nursing students (Carey et al., 2018; Cust & Guest, 2019), and may be preferred to professional help (Morton, 2022). Studies concerning nursing students outside of their country of origin were not identified.…”
Section: Discussionmentioning
confidence: 99%